Delineation of Groundwater Storage and Recharge Potential Zones Using Multi-Influencing Factors (MIF) Method: Application in Synclinal Coastal Basin of Essaouira (Western High Atlas of Morocco) - Agli, Saloua; Ahmed, Algouti; Abdellah, Algouti; Abdelouahed, Farah; Moujane, Said; Salma, Kabili; Maryam, Errami (Geomatics and Environmental Engineering, 2024)
Unpredictable rainfall caused by climate change and pollution directly impacts groundwater demand, making the exploitation of groundwater reserves necessary. To achieve this, a study in the synclinal basin of Essaouira (Western High Atlas) used GIS, remote sensing, and the Multi-Influencing Factors (MIF) method, to identify areas ideal for the installation of productive wells. An overlay analysis created a groundwater potential zone (GWPZ) map, showing 30% of the basin with high potential, 51% with moderate potential, and 19% with low to very low potential. The groundwater potential zone map was validated using geophysical surveys, piezometric data, and well water levels, showing a 69.3% prediction accuracy with the ROC curve.